Diterpenoids from Rabdosia Japonica - XIANG, ZHAO-BAO; XU, YI-XIN; JIN, YONG-SHENG; SHEN, YANG; WANG, HOU-PENG; CHEN, HAI-SHENG (Asian Journal of Chemistry, 2010)
Two new diterpenoids were isolated along with 5 known diterpenoids from the whole plant of Rabdosia japonica (Burm. f.) Hara var. glaucocalyx (Maxim.) Hara and their structures were elucidated on the basis of spectroscopic methods and the two new diterpenoids named glaucocalyxin F (1) and glaucocalyxin X (2), respectively.